A Bird’s Eye View of the Systematics of Convolvulaceae: Novel Insights From Nuclear Genomic Data - Simões, Ana Rita G.; Eserman, Lauren A.; Zuntini, Alexandre R.; Chatrou, Lars W.; Utteridge, Timothy M. A.; Maurin, Olivier; Rokni, Saba; Roy, Shyamali; Forest, Félix; Baker, William J.; Stefanović, Saša (Frontiers in Plant Science, 2022)
Convolvulaceae is a family of c. 2,000 species, distributed across 60 currently recognized genera. It includes species of high economic importance, such as the crop sweet potato (Ipomoea batatas L.), the ornamental morning glories (Ipomoea), bindweeds (Convolvulus), and dodders, the parasitic vines (Cuscuta). Earlier molecular phylogenetic studies based predominantly on chloroplast markers have provided a framework for systematic studies of the family, but uncertainty remains at the level of the relationships among subfamilies, tribes, and genera, hindering evolutionary inferences and taxonomic advances. One of the remaining enigmas has been the relationship of Cuscuta to the rest of Convolvulaceae. Other enduring examples of unresolved issues within the family include the monophyly and relationships within the ‘bifid-style’ clade (Dicranostyloideae) and the relative positions of Erycibe and Cardiochlamyeae. In this study, we explore novel phylogenomic data generated using the Angiosperms353 kit, to resolve some of these remaining uncertainties within Convolvulaceae, and test monophyly and position of subfamilies and tribes towards an improved classification.